Politik Hukum Dalam Pembentukan Hukum Waris Nasional di Indonesia: Antara Keberagaman Sistem dan Tuntutan Unifikasi - Muhsin; Dediansyah; Zuhrah (Maqasid: Jurnal Studi Hukum Islam, 2025)
This study discusses legal politics in the formation of national inheritance law in Indonesia, focusing on the challenges of diverse inheritance law systems and the demand for unification. Indonesia has a pluralistic inheritance law system consisting of customary inheritance law, Islamic inheritance law, and civil inheritance law, all of which coexist and are applied based on social and religious backgrounds. The process of forming national inheritance law, which is expected to accommodate this diversity, faces various obstacles, such as differences in values, ideologies, and conflicting political interests. The research method used is a qualitative approach with documentary studies and case studies. The data utilized includes legal documents, court decisions, parliamentary meeting minutes, and relevant academic literature. The research findings show that despite unification efforts through drafts of laws and court decisions, significant challenges remain in harmonizing the various inheritance law systems in force. This study concludes that the formation of national inheritance law requires a compromise between existing legal systems, taking into account political dynamics, public interests, and principles of justice that are fair and equitable. Keywords: legal politics, national inheritance law, legal pluralism, unification, harmonization.